‘Secularisation of the word’: the semiotic ideologies of Russian Orthodox bloggers - Leonard, Stephen Pax (Journal for the study of religions and ideologies, 2021)
What does it mean to lose a ‘divine’ language? The liturgical language used in the Russian Orthodox Church (ROC) (Church Slavonic) is perceived to index an authenticity because it is believed to be attuned to the inner, spiritual life of the worshipper. This article analyses the metasemiotic framing used by Russian Orthodox ‘traditionalist’ bloggers when discussing the status and fate of the ‘divine language’. In accordance with the aesthetic consciousness of a traditionalist, the liturgical language has been semiotized for the linguistic code is perceived consciously and subjectively as a sign. Some traditionalists equate liturgical language reform with ‘disenchantment’ (for them an ingredient of secular modernity), and they discuss this disenchantment as ‘a semiotic event’. More generally, this article shows how so-called ideologies of worship mediate semiotic assumptions made about linguistic codes.